Value priorities of the Finnish farmers—Time to stop thinking of farmers as inherently conservative and traditional - Sorvali, Jaana; Kaseva, Janne; Vainio, Annukka; Verkasalo, Markku; Peltonen‐Sainio, Pirjo (John Wiley, 2022)
Farming communities are becoming more heterogeneous and multifunctional due to various structural and environmental changes. However, it is not known if farmers' values have also become more heterogeneous. We wanted to explore potential heterogeneity in farmers' value priorities in detail across different farmer groups in Finland using the refined Schwartz theory of 19 basic human values. A representative sample of 4,401 Finnish farmers responded to a survey in 2018. The data were analysed with multidimensional scaling, confirmatory factor analysis and one-way analysis of variance. The results show that farmers' values were heterogeneous, and differences were associated with socio-demographic characteristics. Our findings confirmed the motivational continuum structure of values, with the exception of societal-value. Security-societal was the most important value for the Finnish farmers. The theory of 19 values proved useful in uncovering value priorities in detail. The security-societal value is more a part of national identity rather than a personal motivational value in the Finnish farming community. The heterogeneity of farmers' values should be considered in more targeted policy planning.
Keywords: maatalous; ilmastonmuutokset; arvot; maanviljelijät; agriculture; farmers; Finland; Schwartz; survey; values; maatalous; ilmastonmuutokset; arvot; maanviljelijät; agriculture; farmers; Finland; Schwartz; survey; values